The gender pay gap in the public and private sector in Germany - magnitude, evolution 2010-2014 and main drivers - Christina Boll; Andreas Lagemann (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2018)
The present study examines, based on the Structure of Earnings Survey (SES) 2010 and 2014, the unadjusted gender pay gap of the public sector (economic sectors O (Public Administration, Defence, and compulsory Social Security) and P (Education)) compared to the private economy. The unadjusted gender pay gap in the public sector stood at 5.6 % in 2014 and was virtually unchanged compared to 2010. The gap in the private economy remained about four times as high. The wage advantage of women over men among part-time workers, both in the public and in the private sector, is due to the relatively high proportion of marginally and temporarily employed workers and the relatively short firm tenure among men. Among fulltime workers, the explained part of the gap is driven by the performance group. The findings once again underline the need to review gender-based access to leading positions in the public sector. The detailed decomposition of the explained part for all workers reveals that the advantageous distribution of performance groups and levels of education, as well as the lower rate of part-time employment among men, explains their earnings advantage. In the private economy, men also benefit from their employment in wage-attractive sectors.
Keywords: 330